2009
DOI: 10.1007/s11605-009-0944-1
|View full text |Cite
|
Sign up to set email alerts
|

A Reduction in Delayed Gastric Emptying by Classic Pancreaticoduodenectomy with an Antecolic Gastrojejunal Anastomosis and a Retrogastric Omental Patch

Abstract: A classic PD combined with an antecolic anastomosis and retrogastric vascular omental patch results in a significant reduction in DGE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 56 publications
4
33
0
2
Order By: Relevance
“…Of note, however, most patients with retrocolic reconstruction in that series underwent pylorus-preserving PD and were compared with a classic PD with antecolic reconstruction. 35 The DGE rate of 14% in the antecolic group undergoing a classic antrectomy is identical to the DGE rate in this study, while the DGE rates in the retrocolic group (21% vs 40%) were much higher, most likely because of pylorus preservation. Hartel et al 10 (not using the ISGPF-DGE definition) reported a DGE rate of 5% vs 24%, also favoring an antecolic reconstruction.…”
Section: Commentssupporting
confidence: 76%
“…Of note, however, most patients with retrocolic reconstruction in that series underwent pylorus-preserving PD and were compared with a classic PD with antecolic reconstruction. 35 The DGE rate of 14% in the antecolic group undergoing a classic antrectomy is identical to the DGE rate in this study, while the DGE rates in the retrocolic group (21% vs 40%) were much higher, most likely because of pylorus preservation. Hartel et al 10 (not using the ISGPF-DGE definition) reported a DGE rate of 5% vs 24%, also favoring an antecolic reconstruction.…”
Section: Commentssupporting
confidence: 76%
“…Several previous studies [8,9] indicated that the surgical technique factors of GJ were related to the incidence of DGE. Over one hundred years ago, Braun [10] introduced a modified technique of GJ, in which an anastomosis between the afferent and efferent limbs of jejunum distal to the gastroenterostomy was performed.…”
Section: Introductionmentioning
confidence: 98%
“…There are much more factors on reconstructive stage effecting on incidence of gastrostasis. It is true for ante-and retrocolic duodenojejunostomy [27,43] or gastrojejunostomy [31] as well as for ante-or retromesenteric passage of intestinal loop for anastomosis. The level of stomach resection also influences oh incidence of this complications [18].…”
Section: Resultsmentioning
confidence: 99%
“…Факторов, связанных с рекон-структивным этапом и влияющих на частоту гастро-стаза, на порядок больше. Это касается впереди-или позадиободочного формирования дуоденоеюноана-стомоза [27,43] или гастроеюноанастомоза [31], а также впереди-или позадимезентериального прове-дения петли тонкой кишки для формирования ана-стомоза. Уровень резекции желудка также влияет на частоту этого осложнения [18].…”
Section: результаты и обсуждениеunclassified